2023
DOI: 10.1002/jsfa.12449
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprecipitates of γ‐cyclodextrin/epigallocatechin‐3‐gallate inclusion complexes as efficient antioxidants for preservation of shrimp surimi products: synthesis, performance and mechanism

Abstract: BACKGROUND Epigallocatechin‐3‐gallate (EGCG) is well known for excellent chain‐breaking antioxidant capability. However, browning by oxidation and aggregation of EGCG is a non‐negligible defect that hinders its applications as an antioxidant in various foodstuffs. Therefore, how to eliminate or mitigate browning efficiently, while retaining functionalities as food additive is a challenge in the food industry. RESULTS Our results demonstrated that EGCG could be anchored within the internal cavity of γ‐cyclodext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For instance, in a 28 day observation by Ho et al, cyclodextrin-based inclusion complexes were found to be effective in alleviating the browning of catechins under the conditions with a relative humidity of 10–75% yet still were observed to collapse, aggregate, as well as brown progressively when exposed to a higher relative humidity of above 85% . A subsequent study in our lab showed that the use of cyclodextrin-based inclusion complexes exhibited excellent mitigation on the auto-browning phenomenon of EGCG within 3 weeks in the preservation of shrimp surimi (with a moisture content of about 75%) . In addition, our investigation indicated that, in the complexes, the arrangement of the inclusion structure as the fundamental unit followed a random mode via the interactions of the outer surface of cyclodextrins and was susceptible to disruption by water molecules .…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…For instance, in a 28 day observation by Ho et al, cyclodextrin-based inclusion complexes were found to be effective in alleviating the browning of catechins under the conditions with a relative humidity of 10–75% yet still were observed to collapse, aggregate, as well as brown progressively when exposed to a higher relative humidity of above 85% . A subsequent study in our lab showed that the use of cyclodextrin-based inclusion complexes exhibited excellent mitigation on the auto-browning phenomenon of EGCG within 3 weeks in the preservation of shrimp surimi (with a moisture content of about 75%) . In addition, our investigation indicated that, in the complexes, the arrangement of the inclusion structure as the fundamental unit followed a random mode via the interactions of the outer surface of cyclodextrins and was susceptible to disruption by water molecules .…”
Section: Introductionmentioning
confidence: 69%
“…9 A subsequent study in our lab showed that the use of cyclodextrin-based inclusion complexes exhibited excellent mitigation on the auto-browning phenomenon of EGCG within 3 weeks in the preservation of shrimp surimi (with a moisture content of about 75%). 10 In addition, our investigation indicated that, in the complexes, the arrangement of the inclusion structure as the fundamental unit followed a random mode via the interactions of the outer surface of cyclodextrins and was susceptible to disruption by water molecules. 10 Therefore, it was speculated that an ordered rather than random arrangement of the inclusion structure could further prolong the intervention effects on the auto-browning of EGCG in high-humidity conditions.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the application and efficacy of EGCG is still limited due to its poor stability. EGCG is susceptible to the effects of temperature, pH, ambient light intensity or metal ions when exposed to air (Song et al ., 2022; Wang et al ., 2023). Numerous studies have reported the encapsulation of EGCG in biomolecules such as proteins (Song et al ., 2022), polysaccharides (Zhou et al ., 2023) and lipids (Shtay et al ., 2019) to form nano‐microcapsules to improve the stability of EGCG, enhance the bioavailability and control the release rate of the encapsulated EGCG.…”
Section: Introductionmentioning
confidence: 99%